2015
DOI: 10.1111/ane.12537
|View full text |Cite
|
Sign up to set email alerts
|

Smoking in Patients with Parkinson's Disease: preliminary striatal DaT-SPECT findings

Abstract: The lower [123I]FP-CIT uptake together with the lower UPDRS-III motor score observed in our current-smokers patients with Parkinson's disease (even taking into account variables that are probably expression of dopaminergic neuron decline and treatment) would support an effect of smoking on dopaminergic synaptic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…An observational study by Itti and co-workers showed a slower decrease in striatal [ 123 I]I-FP-CIT binding in 6 PD patients on nicotine therapy (-4%) than expected in PD patients (-10% per year) [ 101 ]. However, Gigante et al found a significantly lower [ 123 I]I-FP-CIT binding in the putamen of 11% in 13 current smokers compared to non-smokers [ 102 ]. Interestingly, the largest study by Thomsen and colleagues on this topic compared 64 non-smokers, 39 ex-smokers and 26 current smokers and found no statistically significant difference in striatal [ 123 I]I-FP-CIT binding between the different groups [ 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…An observational study by Itti and co-workers showed a slower decrease in striatal [ 123 I]I-FP-CIT binding in 6 PD patients on nicotine therapy (-4%) than expected in PD patients (-10% per year) [ 101 ]. However, Gigante et al found a significantly lower [ 123 I]I-FP-CIT binding in the putamen of 11% in 13 current smokers compared to non-smokers [ 102 ]. Interestingly, the largest study by Thomsen and colleagues on this topic compared 64 non-smokers, 39 ex-smokers and 26 current smokers and found no statistically significant difference in striatal [ 123 I]I-FP-CIT binding between the different groups [ 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…Diagnosis of PD is only possible through clinical signs and symptoms and by neuropathological findings at postmortem examination. By using a dopamine transporter single photon emission computed tomography (DaT-SPECT), we recently reported a widespread reduced striatal uptake in PD patients [2,3]. Nevertheless, there is no specific laboratory test available for PD, therefore, selective biomarkers to assist in the diagnosis of PD are needed.…”
Section: Introductionmentioning
confidence: 99%